LECTURA SIN PALABRAS. LA TRANSMISIÓN DE LA IDEOLOGÍA A TRAVÉS DEL DOCUMENTO ICONOGRÁFICO: EL EJEMPLO DE LA GEMA AUGÚSTEA DE VIENA - Alfaro Giner, Carmen (Antigüedad y Cristianismo, 1995)
The present article offers a view of the value which certain art pieces have as historical documents. So a thorough study is made of the different symbolic elements of a piece of great iconographic interest, the Gemma Augustea in the Kunsthistorisches Museum of Vienna.